PETA STRATEGI IT BALANCED SCORECARD DI AMIK BSI TASIKMALAYA - Bambang Kelana Simpony; Dwiza Riana (IJCIT (Indonesian Journal on Computer and Information Technology), 2016)
Abstract - Implementation of the development  Information and Communication Technology (ICT) in higher education goes very fast and must be supported by structuring the management of ICT itself.  ICT application must also comply with the objectives, vision and mission of the organization. So it takes analysis factors that influence the formation of a planning strategy or ICT system which is in accordance with the business strategy. AMIK BSI Tasikmalaya now using Information Systems (IS) and Information Technology (IT) as a means of management services to students and employees, these applications are still experiencing problems and shortcomings. IS and IT in order to be given completely in accordance with the vision and mission of the organization is needed in providing strategic analysis services in accordance with the organization's strategy. How to design a strategy map using IT Balanced Scorecard (BSC) by analyzing the vision, mission and strategic objectives of the institution (SWOT Analysis), compiled IT perspective BSC, strategy maps compiled and determine Key Performance Indicator (KPI). The results showed that the technology information in AMIK BSI Tasikmalaya in ministry strategy there should be enhanced, characterized by a strategy map is generated based on four perspectives of the IT BSC all generate strategic proposals.Keywords: IT BSC, Key Performance Indicator, Strategy Map, SWOT Abstrak - Pelaksanaan pembangunan Teknologi Informasi dan Komunikasi (TIK) dalam pendidikan tinggi berjalan sangat cepat dan harus didukung dengan penataan manajemen TIK itu sendiri. Aplikasi TIK juga harus sesuai dengan tujuan, visi dan misi organisasi. Jadi dibutuhkan faktor analisis yang mempengaruhi pembentukan strategi perencanaan atau sistem TIK yang sesuai dengan strategi bisnis. AMIK BSI Tasikmalaya sekarang menggunakan Sistem Informasi (SI) dan Teknologi Informasi (TI) dalam memberikan pelayanan kepada mahasiswa dan karyawan, aplikasi ini masih mengalami masalah dan kekurangan. SI dan TI yang dibuat harus benar-benar sesuai dengan visi dan misi organisasi, ini diperlukan dalam memberikan layanan analisis strategis sesuai dengan strategi organisasi. Selanjutnya bagaimana merancang sebuah peta strategi menggunakan Balanced Scorecard (BSC) dengan menganalisis visi, misi dan tujuan strategis dari lembaga (Analisis SWOT), menyusun perspektif IT BSC, menyusun peta strategi dan menentukan Key Performance Indicator (KPI). Hasil penelitian menunjukkan bahwa teknologi informasi di AMIK BSI Tasikmalaya dalam strategi pelayanannya ada yang harus ditingkatkan, ditandai dengan peta strategi yang dihasilkan berdasarkan empat perspektif dari IT BSC semuanya menghasilkan proposal strategis.Kata kunci: IT BSC, Key Performance Indicator, Peta Strategi, SWOT